Roles of Islamic Business Ethics in the Formation of Internal Organisational Culture: A Qualitative Approach of Muslims’ SMEs in the UK - Alanazi, Tawfeeq. M.; Hassan, Hend. S. (International Journal of Economics, Business and Management Studies, 2018)
This research aims to explore the elements of Islamic business ethics and the roles which shape particular types of organisational culture amongst Small and Medium Enterprises (SMEs) that are owned and/or managed by Muslims in the UK. A qualitative approach has been adopted, beginning with a conceptual and theoretical model reflecting the authors’ research methodology approach. Subsequently, a set of in-depth, semi-structured interviews was conducted. The findings of the study reveal that elements of Islamic business ethics contribute widely to shaping a particular type of organisational culture amongst Muslim SMEs in the UK. Moreover, on the one hand, mercenary type of organisational culture is the dominant culture amongst Muslim SMEs in the UK. On the other hand, within a communal type of organisational culture, people are very sociable and concerned about each other, which will be reflected on the organisation’s fine performance. The value of this research is derived from its ability to grasp the formation and impact of organisational culture which is one of the main subjects in business management and organisation studies. The research presents various aspects and features of internal organisational culture formation, impact and possibility to change.